PENDAPATAN USAHATANI TANAMAN JAGUNG (Zea mays Sp) DI DESA RANTAU MAKMUR KECAMATAN BERBAK KABUPATEN TANJUNG JABUNG TIMUR - Rogayah Rogayah; Wiwin Alawiyah; Arfandi . (Universitas Batangahari Jambi, 2017)
AbstractTanjung Jabung Timur Regency has a predicate as the 4th planting area of corn commodities in Jambi Province. This provides an opportunity for farmers to focus their production in accordance with consumer demand and the business makes as a source of farmer income. Corn commodity development In Rantau Makmur Village, Berbak District has high economic value. The objective of this research is to know the description of farming activities, the use of input and production cost and the amount of income farming. The number of samples that taken in this study (30 farmers) applies simple random sampling methode. The results of this research note that the input productions used in this farming consisted of seeds, labors, fertilizer, pesticide/insecticide and several farm equipments. The used by the variety of bisi 2 were bought from an agriculture shop. male and female laborers come from inside and outside of their family. Fertilizer, pesticide/insecticide and equipment efforts by the farmer itself. It can be concluded that the amount of income of corn farming gives an average of Rp. 4.682.301,37/Ha/periode, or it is equivalent with Rp. 1.560.767,12/month of each family member. So it can be concluded that corn farming in Rantau Makmur Village, Berbak District Tanjung Jabung Timur Regency is still small lower than the region income standart of Rp. 2.020.000.Keyword : Income, Farming, Corn.AbstrakKabupaten Tanjung Jabung Timur pengembangan komoditas jagung terluas peringkat ke 4 dalam Propinsi Jambi. Hal ini memberi peluang bagi petani jagung untuk memfokuskan produksinya pada jagung. Di Desa Rantau Makmur Kecamatan Berbak pengembangan komoditas jagung memiliki nilai ekonomis yang cukup tinggi. Penelitian ini dilakukan untuk melihat bagaimana gambaran tentang usahatani jagung, bagaimana penggunaan input dan biaya produksi, seberapa besar pendapatan usahataninya. Jumlah sampel yang diambil dalam penelitian ini adalah sebanyak 30 rumah tangga petani (RTP) secara acak sederhana (simple random sampling). Dari hasil penelitian diketahui bahwa input produksi yang digunakan terdiri dari bibit varietas bisi 2, tenaga kerja, pupuk, obat-obatan dan peralatan usahatani. Besarnya pendapatan usahatani adalah Rp. 4.682.301,37/Ha/MT, kalau dihitung perkapita dengan rata–rata jumlah anggota keluarga petani 3 orang maka besar pendapatan sebesar Rp. 1.560.767,12/Bln. Jadi dapat disimpulkan bahwa usahatani jagung di Desa Rantau Makmur Kecamatan Berbak Kabupaten Tanjung Jabung Timur masih kecil dari UMR sebesar Rp. 2.02.000 terhadap pendapatan keluarga petani.Kata Kunci : Pendapatan, Usahatani, Jagung